Pd/Fe3O4 Nanofibers for the Catalytic Conversion of Lignin-Derived Benzyl Phenyl Ether under Transfer Hydrogenolysis Conditions - Angela Malara (Catalysts, 2019)
Novel magnetite-supported palladium catalysts, in the form of nanofiber materials, were prepared by using the electrospinning process. Two different synthetic techniques were used to add palladium to the nanofibers: (i) the wet impregnation of palladium on the Fe3O4 electrospun support forming the Pd/Fe3O4[wnf] catalyst or (ii) the direct co-electrospinning of a solution containing both metal precursor specimens leading to a Pd/Fe3O4[cnf] sample. The obtained Pd-based Fe3O4 nanofibers were tested in the transfer hydrogenolysis of benzyl phenyl ether (BPE), one of the simplest lignin-derived aromatic ethers, by using 2-propanol as H-donor/solvent, and their performances were compared with the analogous impregnated Pd/Fe3O4 catalyst and a commercial Pd/C. A morphological and structural characterization of the investigated catalysts was performed by means of SEM-EDX, TGA-DSC, XRD, TEM, H2-TPR, and N2 isotherm at 77 K analysis. Pd/Fe3O4[wnf] was found to be the best catalytic system allowing a complete BPE conversion after 360 min at 240 °C and a good reusability in up to six consecutive recycling tests.